FEASIBILITY OF SUBSTITUTING COCOPEAT WITH RICE HUSK AND SAW DUST COMPOST AS A NURSERY MEDIUM FOR GROWING VEGETABLE SEEDLINGS ABLE SEEDLINGS - DEBASIS MITRA, KOMAL SHARMA, T. R. RUPA AND G. SELVAKUMAR, T. K. RADHA , A. N. GANESHAMURTHY, (The Bioscan, 2018)
The present study reports the feasibility of partial substitution of coir dust in cocopeat production with sawdust and rice husk as a nursery media. Compost was produced by mixing different ratios of raw coir dust, saw dust and rice husk following ICAR-IIHR protocol. The chemical analysis of compost samples showed that among different treatments, substitution with 25% rice husk i.e.,T5 (75% Raw coir dust + 25% Rice husk) recorded lowest C/N ratio (37.13), phenols and tannins (155 mg/100gm) at 30 days of composting. Further the effect of these composts were studied on germination and survival rate of tomato, chilli, cabbage, cauliflower and brinjal crops along with the application of 5% soil less mycorrhiza in pro trays. The highest germination percentage and seedlings survival were observed in T5 (75% Raw coir dust + 25% Rice husk) in all the vegetables. The study showed that substitution with 25% rice husk produced the best compost for nursery media and produced intact plugs of seedlings of different vegetables compared to other treatments.